2009
DOI: 10.1080/15427520902976471
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Morpho-Physiological Traits in Segregating Populations of Interspecific Hybrid Rice Under Stress and Non-Stress Conditions

Abstract: Drought is one of the major constraints for rice (Oryza sativa L.) production in the rainfed ecologies in Sub-Saharan Africa. The objectives of this study were to investigate the genetic effects of morpho-physiological traits controlling drought-stress tolerance. Five Oryza glaberrima genotypes, four interspecific inbred lines, two interspecific hybrids, and two O. sativa lines and their progenies from a North Carolina II mating design were evaluated at ICRISAT in Mali under drought and fully irrigated condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…To conclude from both these fields and the previous biotron The results of the present study indicate spikelet fertility and weight of 100 grains as important grain yield components having an impact on total grain yield. These findings correspond well with previous research, and thus, these parameters can serve as selection criteria for high grain yield under both drought and well-watered conditions (Efisue, Tongoona, Derera, Ubil, & Oselebe, 2009;Panja, Garg, Mandi, Sarkar, & Bhattacharya, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…To conclude from both these fields and the previous biotron The results of the present study indicate spikelet fertility and weight of 100 grains as important grain yield components having an impact on total grain yield. These findings correspond well with previous research, and thus, these parameters can serve as selection criteria for high grain yield under both drought and well-watered conditions (Efisue, Tongoona, Derera, Ubil, & Oselebe, 2009;Panja, Garg, Mandi, Sarkar, & Bhattacharya, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge of heritability of a trait is important because it determines the extent to which plant improvement through selection is possible. A parent-offspring regression gives heritability estimates and provides a measure of GCA (General Combining Ability) of parents for a trait [17]. The yield components of genotypes should have sufficient genetic variation and be highly heritable to ease selection process in population improvement.…”
Section: Heritability Estimatesmentioning
confidence: 99%
“…Four genomic regions, which are high QTLs density have been reported [16a,]. The rice species O. glaberrima has good agronomic traits [17], Fe toxicity tolerance QTLs has been identified from O. glaberrima using an interspecific backcross population [18b], these could be used in rice population development for good agronomic traits. The work on iron toxicity tolerance QTL analysis has been found to be limited with 203 QTLs from 16 mapping populations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also indicated abscisic acid accumulation, variation in root development, carbon isotope discrimination, and proline accumulation which regulate the crop's differential performance under water-limited conditions [6][7][8][9]. On the other hand, the mechanisms underlying these traits are regulated by several genes within the cassava genome which can be targeted in breeding to select improved cassava genotypes for drought-prone ecologies [10][11][12]. For instance, 10 candidate genes have been found to be associated with drought tolerance mechanisms in cassava which are upregulated under stress to mitigate the negative effects of moisture stress [6].…”
Section: Introductionmentioning
confidence: 99%